The cost of improving nutritional outcomes through food‐assisted maternal and child health and nutrition programs in Burundi and Guatemala - Heckert, Jessica; Leroy, Jef L.; Olney, Deanna K.; Ritcher, Susan; Iruhiriye, Elyse; Ruel, Marie T. (John Wiley & Sons, 2020)
Evidence on the cost‐effectiveness of multisectoral maternal and child health and nutrition programmes is scarce. We conducted a prospective costing study of two food‐assisted maternal and child health and nutrition programmes targeted to pregnant women and children during the first 1,000 days (pregnancy to 2 years). Each was paired with a cluster‐randomized controlled trial to evaluate impact and compare the optimal quantity and composition of food rations (Guatemala, five treatment arms) and their optimal timing and duration (Burundi, three treatment arms). We calculated the total and per beneficiary cost, conducted cost consequence analyses, and estimated the cost savings from extending the programme for 2 years. In Guatemala, the programme model with the lowest cost per percentage point reduction in stunting provided the full‐size family ration with an individual ration of corn–soy blend or micronutrient powder. Reducing family ration size lowered costs but failed to reduce stunting. In Burundi, providing food assistance for the full 1,000 days led to the lowest cost per percentage point reduction in stunting. Reducing the duration of ration eligibility reduced per beneficiary costs but was less effective. A 2‐year extension could have saved 11% per beneficiary in Guatemala and 18% in Burundi. We found that investments in multisectoral nutrition programmes do not scale linearly. Programmes providing smaller rations or rations for shorter durations, although less expensive per beneficiary, may not provide the necessary dose to improve (biological) outcomes. Lastly, delivering effective programmes for longer periods can generate cost savings by dispersing start‐up costs and lengthening peak operating capacity.